Images of StrategyImages of Strategy, edited by CummingsStephen and WilsonDavid. Oxford: Blackwell, 2003 - Guth, William D. (Academy of Management Review, 2004)
The article presents a review of the book “Images of Strategy,” edited by Stephen Cummings and David Wilson.